PENGARUH BRAND EQUITY, HARGA DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN VAPE (Studi PadaVape Store 5Time) - Bahtiar, Ahmad; Rahardja, Edy (Diponegoro Journal of Management, 2017)
Problems that occur is the sale of vape with the original brand does not show increase from month to month, exactly in May to July decreased. Though currently vape trend is getting in demand so consumers who are looking for vape pretty much. Based on the results of prasurvey conducted, it appears that the decline in sales is allegedly caused by the strength of the original brand is not very good, the original vape price is considered expensive and the distribution of goods that are less evenly distributed. This study aims to analyze the influence of brand equity, price and distribution of the original vape purchase decision in Semarang.The population used in this study is all Vape consumers in Semarang. The sampling technique used is purposive sampling. Sampling criteria were 96 vape consumer in Semarang. Methods of data collection in this study using questionnaires. Methods of data analysis using multiple linear regression analysis.Based on the results of brand equity, price and distribution have a positive effect on the purchase decision of original vape in Semarang. The original vape purchase decision in Semarang can be explained by brand equity, price and distribution of 81%.